Revealing plant growth-promoting mechanisms of Bacillus strains in elevating rice growth and its interaction with salt stress - Ali, Qurban; Ayaz, Muhammad; Mu, Guangyuan; Hussain, Amjad; Yuanyuan, Qiu; Yu, Chenjie; Xu, Yujiao; Manghwar, Hakim; Gu, Qin; Wu, Huijun; Gao, Xuewen (Frontiers in Plant Science, 2022)
Soil salinity is a major environmental stress that has been negatively affecting the growth and productivity of rice. However, various salt-resistant plant growth-promoting rhizobacteria (PGPR) have been known to promote plant growth and alleviate the damaging effects of salt stress via mitigating physio-biochemical and molecular characteristics. This study was conducted to examine the salt stress potential of Bacillus strains identified from harsh environments of the Qinghai-Tibetan plateau region of China in rice. The Bacillus strains NMTD17, GBSW22, and FZB42 were screened for their response under different salt stress conditions (1, 4, 7, 9, 11, 13, and 16 %). The screening analysis revealed strains NMTD17, GBSW22, and FZB42 to be high-salt tolerant, moderate-salt tolerant, and salt-sensitive, respectively. The NMTD17 strain produced a strong biofilm, followed by GBSW22 and FZB42. The expression of salt stress-related genes in selected strains was also analyzed through qPCR in various salt stress concentrations. Further, the Bacillus strains were used in pot experiments to study their growth-promoting ability and antioxidant activities at various concentrations (0, 100, 150, and 200 mmol). The growth-promoting traits’ analysis in rice exhibited that NMTD17 had a highly significant effect and GSBW22 had a moderately significant effect in comparison with FZB42. The highly resistant strain NMTD17 that stably promoted rice plant growth was further examined for its function in the composition of rhizobacterial communities. The inoculation of NMTD17 increased the relative abundance and richness of rhizobacterial species. These outcomes propose that NMTD17 possesses the potential of PGPR traits, antioxidants enzyme activities, and reshaping the rhizobacterial community that together mitigates the harmful effects of salinity in rice plants.